A Qualitative Study on the Process of the Mental Health Assessment and Intervention after the Sewol Ferry Disaster: Focusing on Survivors among Danwon High School Students - Lee, Mi-Sun (Soa Chongsonyon Chongsin Uihak, 2018)
OBJECTIVES: This study aimed to identify the process of psychosocial assessment, the experience of intervention, and the improvement after the disaster that Danwon high school students survived from the sinking of the Motor Vessel (MV) Sewol in South Korea on April 16, 2014. METHODS: We conducted in-depth qualitative research using individual interviews from January to February 2017. Twenty-one of 75 Danwon high school students survived by the MV Sewol disaster were studied. Two interviewers participated in the in-depth interview. Interviews were transcribed verbatim, coded, and analyzed through content analysis based on psychosocial assessment and intervention after the disaster. RESULTS: Twenty-one participants were 20 years old, where 10 were male (47.62%), and 11 were female (52.38%). More than 75% of the interviewed students felt that mental health services were needed, and more than 85% required mental health assessments. Regarding psychiatric symptoms, the students reported that they suffered depression and insomnia (19.05%), anxiety (14.29%), nightmares and phobias (9.52%), and difficulties regarding concentration, aggression, and game addiction (4.76%). CONCLUSION: Despite survivors experiencing the same disaster, there were differences in their responses to mental health assessments and interventions experienced during the three years, and conflicting opinions were reported. In planning future evaluations and interventions, it is necessary for strategies to cope with flexibly to consider the characteristics and symptoms of the survivors while maintaining principles.